Real Time Detection and Association of Helicobacter Pylori in Oral Squamous Cell Carcinoma - Kandasamy Murugan; Kesavaram Padmavathy; Philips Mathew; Nalini Ashwath; R C Neil Ananth; T Saravanan (Journal of Indian Academy of Oral Medicine and Radiology, 2025)
Background: Helicobacter pylori is a recognized pathogen associated with gastric carcinoma, but its potential role in oral squamous cell carcinoma (OSCC) remains underinvestigated. Objective: To evaluate the prevalence of H. pylori in OSCC patients and compare it with healthy controls, assessing its potential etiological role in OSCC. Methods: This study included 30 participants, OSCC (n = 15) patients and healthy controls (n = 15). Unstimulated saliva was collected from all the study participants, and DNA was extracted, aliquoted, and stored. H. pylori HPUreA gene was detected in the saliva samples by real-time PCR. Histopathological confirmation of the clinical diagnosis of OSCC was performed for the patient group. Statistical analysis was performed to compare the prevalence of H. pylori between the groups and the associations with clinical variables, including lifestyle factors such as smoking and betel nut chewing. Results: Statistically significant difference (P < 0.05) was observed in the prevalence of H. pylori between OSCC patients (73.33%) and the healthy controls (26.67%) who tested positive. Nevertheless, no difference in the mean CT value for the positive samples in the control group Vs OSCC group (36.6 ± 1.26 Vs 37.19 ± 1.31) was not statistically significant (P > 0.05). Conclusion: The findings suggest a strong association between H. pylori and OSCC, highlighting the potential role of the bacterium in oral carcinogenesis and warranting further research to understand the underlying mechanisms.